Implementation of Laravel Framework in Development Web-Based Employee Performance Monitoring Information System - Ridho Van Rizki; Leni Marlina; Hendry (Cattleya Darmaya Fortuna, 2026)
This study aims to develop a web-based employee performance monitoring information system at UPT PEPENDA Medan Selatan to address data management issues that are still carried out manually, such as processing delays and low data accuracy. The method used in this study is Prototype, which allows system development through the creation of an initial model that can be evaluated gradually by users. The system was developed using the Laravel framework with a Model-View-Controller (MVC) architecture and supported by a MySQL database. The results of the study show that the system is able to automate the employee performance monitoring process, accelerate data processing, and produce structured and real-time reports. Thus, the system built can improve efficiency, accuracy, and transparency in managing employee performance monitoring.